Standardizing the surgical management of benign ovarian tumors in children and adolescents: A best practice Delphi consensus statement. Issue 4 (4th February 2022) - Braungart, Sarah; Williams, Cara; Arul, Suren G.; Bambang, Katerina; Craigie, Ross James; Cross, Kate Mary; Dick, Alistair; Hammond, Philip; Okoye, Bruce; Rogers, Timothy; Losty, Paul Damian; Glaser, Adam; et al.
Abstract: Aim: No widely agreed consensus protocols exist for the management of benign ovarian tumors (BOT) in children. This presents a substantial risk for suboptimal management. We aimed to generate multispecialty consensus guidance to standardize surgical management and provide a clear follow‐up protocol for children with BOTs. Methods: Prospective two‐round confidential e‐Delphi consensus survey distributed among multispecialty expert panel; concluded by two semistructured videoconferences. Main results: Consensus was generated on these core outcome sets: preoperative/intraoperative management; follow‐up; adolescent gynecology referral. (1) Children with BOTs should receive the same management as other patients with potentially neoplastic lesions: Preoperative discussion at a pediatric oncology multidisciplinary meeting to risk stratify tumors, and management by health professionals with expertise in ovarian‐sparing surgery and laparoscopy. (2) Ovarian‐sparing surgery for BOTs should be performed wherever possible to maximize fertility preservation. (3) Ovarian masses detected during emergency laparoscopy/laparotomy should be left in situ wherever feasible and investigated appropriately (imaging/tumor markers) before resection. (4) Follow‐up should be undertaken for all patients after BOT resection. Patients should be offered referral to adolescent gynecology to discuss fertility implications. Conclusion: This best practice Delphi consensus statement emphasizes the importance of managing children with BOTs through a well‐defined oncological MDT strategy, in order to optimize risk stratification and allow fertility preservation by ovarian‐sparing surgery wherever possible.